Eksistensi Pondok Pesantren dalam Penguatan Moderasi Beragama - Cipto Handoko; Nurul Fadilah (TAFAHUS: JURNAL PENGKAJIAN ISLAM, 2022)
Diversity in Indonesia is a fact and a necessity that characterizes the Indonesian nation, this diversity will eventually open for division if it is not addressed wisely. Therefore this study aims to examine the existence of Islamic boarding schools in strengthening religious moderation. The research method used is literature study which is a type of qualitative research with content analysis. The results of the study show that Islamic boarding schools play an important role in strengthening the religious moderation of students as well as the community through their learning and preaching activities. The values ​​of religious moderation that can be instilled in Islamic boarding schools are tolerance, respect and preservation of local culture and national commitment. So that the awareness to implement religious moderation will optimally